Induction of Pigmentation in Nonproliferating Cells of Serratia marcescens by Addition of Single Amino Acids - Williams, Robert P. (1971)
Addition of casein hydrolysate to suspensions of washed, nonpigmented, nonproliferating Serratia marcescens incubating at 27 C induced biosynthesis of prodigiosin. Four amino acids of casein hydrolysate, dl-aspartic acid, l-glutamic acid, l-proline, and l-alanine caused formation of pigment when added individually. dl-Ornithine also was effective. Optimal concentrations for maximal pigmentation were 5 to 10 mg/ml; at these high concentrations, d-serine also induced biosynthesis of some prodigiosin. dl-Alanine and -ornithine were as effective as the l-iosomers, but l-glutamic acid and l-proline gave better responses than their racemic mixtures. Kinetics of prodigiosin biosynthesis after addition of dl-alanine (20 mg/ml) were similar to those of cells suspended in 0.2% casein hydrolysate. The other amino acids were less effective. Addition of 5 mg of dl-alanine or casein hydrolysate per ml to minimal medium increased by 30% the amount of prodigiosin formed by growing cells after incubation for 7 days at 27 C. Cultures grown for 7 days at 27 C in 0.2% casein hydrolsate formed more prodigiosin than did suspensions of nonproliferating cells containing individual amino acids or casein hydrolysate. However, more pigment was produced by cells suspended in l-alanine (5 mg/ml) or l-proline (10 mg/ml) than when suspended in 0.4% natural or synthetic casein hydrolysate. Filtrates from suspensions of nonproliferating cells forming pigment in l-proline induced more rapid formation of prodigiosin, but filtrates from suspensions in dl-alanine did not. The data supported the hypothesis that pyrrole groups of prodigiosin may be synthesized from 5-carbon amino acids such as proline, ornithine, aspartic, and glutamic acids, but the role of alanine is unknown.